The itinerary of opera companies performing in the cities of Desterro (SC) and Rio Grande (RS) between 1850 and 1880 (Orfeu, 2025)
This article presents the transit of lyrical companies on the route of the cities of Desterro (SC) and Rio Grande (RS) between 1850 and 1880. The objective is to elucidate the foundation and musical programming of these groups that toured the coast when they performed lyrical seasons in the cities studied. In this way, I use the concept of civilizing process of Norbert Elias (1994; 2001) as a guideline to verify the construction of a prevailing taste on theater stages and the type of repertoire exhibited by musical groups during their tours throughout Brazil.
Keywords: opera companies; opera; repertoire; musical historiography